Numerical Simulation of Fifth order Linear and Nonlinear BVPs via Haar wavelet method - Nidhi Prabhakar; Rajan Singh; B K Singh; Nidhi Tiwari; Deepak Sharma; Anshul Dubey (Utilitas Mathematica, 2025)
In this research article, the numerical solution of fifth order boundary value problems (BVPs) is presented. For this purpose, application of the Haar wavelet method has been discussed. In this method, space derivative terms are approximated using truncated Haar wavelet series. The present method is tested on fifth order linear and nonlinear BVPs. The accuracy of the proposed technique is demonstrated through two numerical examples, taken from existing literature. The present approximate results are shown through tables and figures. The numerical solutions demonstrate the high accuracy of the present method.